CONDITIONS AND EFFECTS OF ENVIRONMENTAL LEGISLATIVE CHANGES: (Twenty years since the beginning of the Europeanization process in the Republic of Serbia) - Todić, Dragoljub C (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
The Europeanization process, conceived as harmonisation of national regulations with EU legislation, is a complex process that is determined by various socio-economic and political conditions. For more than nine years, the Republic of Serbia (RS) has been a European Union (EU) candidate country. The procedure for preparation and adoption of regulations has been partly changed in RS as a response to the defined objectives. However, the procedure still does not provide full perception and consideration of the specific conditions and possibilities of the RS’s economy and the society. Additionally, the harmonization and implementation process is faced with a number of other challenges. By taking as an example the environmental legislation of the RS and by evaluating the conditions under which the environmental laws were prepared and implemented, the paper explains the effects and limitations of the Europeanization process. The data shows that there are some results in the harmonization and implementation of regulations that are in line with EU regulations. Almost all key environmental laws have been adopted, as well as a huge number of bylaws. However, the huge costs of implementation represent one of the long-term obstacles to achieving the goals of Europeanization.